2000
DOI: 10.1097/00006982-200001000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Topical Anesthesia in Posterior Vitrectomy

Abstract: This technique avoids the risk of globe perforation, retrobulbar hemorrhage, and prolonged postoperative akinesia of the eye. With appropriate case selection, topical anesthesia is a safe and effective alternative to peribulbar or retrobulbar anesthesia in three-port pars plana vitrectomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 0 publications
2
30
0
3
Order By: Relevance
“…Yepez et al published a prospective study in 134 eyes operated with standard 20-gauge vitrectomy under topical anaesthesia (4% lidocaine drops) and preoperative or intraoperative sedation with various vitreoretinal diseases [2]. According to the authors all patients experienced mild pain or discomfort during pars plana sclerotomies, external bipolar cautery, and conjunctival closure.…”
Section: Introductionmentioning
confidence: 99%
“…Yepez et al published a prospective study in 134 eyes operated with standard 20-gauge vitrectomy under topical anaesthesia (4% lidocaine drops) and preoperative or intraoperative sedation with various vitreoretinal diseases [2]. According to the authors all patients experienced mild pain or discomfort during pars plana sclerotomies, external bipolar cautery, and conjunctival closure.…”
Section: Introductionmentioning
confidence: 99%
“…Para lograr acinesia, deben ser inhibidos los impulsos nerviosos que llegan a los músculos extraoculares, lo cual de forma tradicional en vitrectomía y facovitrectomía se logra mediante el uso de bloqueo retro-o peribulbar. Dicho objetivo no se consigue con la anestesia tópica, ya que esta solo afecta las terminaciones del nervio trigémino que llegan a la conjuntiva y córnea; pero mediante la anestesia intracameral se logra inhibir la sensibilidad del segmento anterior, lo que disminuye la incomodidad que puede experimentar el paciente durante la manipulación intraocular, permitiendo una cirugía más rápida con la eliminación de los riesgos que implican el bloqueo retrobulbar o peribulbar 29 . Para utilizar este tipo de anestesia se debe seleccionar de manera adecuada al paciente ideal, así como un procedimiento quirúrgico que no demande demasiada manipulación y tiempo quirúrgico, y que pueda realizarse de manera rápida, permitiendo al paciente mantener su capacidad de parpadeo y movilidad ocular.…”
Section: Discussionunclassified
“…A variety of methods have been described. [8][9][10][11][12][13][14][15][16][17] Advantages of LA over GA include more rapid patient recovery; however also there are some procedures where having an awake patient who is able to cooperate and follow instructions can be helpful. In PRP treatment, the retention of motility such that the patient is able to move the eye around on request leads to an easier view of the peripheral retina with less need for indenting, less conjunctival trauma, and more complete peripheral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthesia has replaced general anaesthesia as it is well tolerated by patients and allows rapid postoperative recovery. [8][9][10][11][12][13][14][15][16] Several local anaesthetic techniques for VR have been used and we have previously reported results using the anterior intraconal technique first described by Wong et al 17 Several authors comment that a potential problem with this technique was that total akinesia was difficult to achieve, which may make perioperative complications more likely. In our hands, however, we found that the intraconal block gave an akinetic block in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%